2015
DOI: 10.3758/s13414-015-0861-1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial constancy of attention across eye movements is mediated by the presence of visual objects

Abstract: Recent studies have shown that attentional facilitation lingers at the retinotopic coordinates of a previously attended position after an eye movement. These results are intriguing, because the retinotopic location becomes behaviorally irrelevant once the eyes have moved. Critically, in these studies participants were asked to maintain attention on a blank location of the screen. In the present study, we examined whether the continuing presence of a visual object at the cued location could affect the allocatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 54 publications
(88 reference statements)
1
20
0
Order By: Relevance
“…Lisi, Cavanagh, & Zorzi (2015) found that presenting objects continuously throughout a saccade allowed for more stable spatiotopic attention than when objects disappeared before a saccade (see also Deubel, Bridgeman, & Schneider, 1998; Deubel, Schneider, & Bridgeman, 1996). Demeyer et al (2010) similarly found the most spatiotopic integration between subtly different stimuli when pre- and post-saccadic stimuli were continuously present across a saccade, and this integration disappeared entirely when they were separated by a blank and a mask.…”
Section: Discussionmentioning
confidence: 94%
“…Lisi, Cavanagh, & Zorzi (2015) found that presenting objects continuously throughout a saccade allowed for more stable spatiotopic attention than when objects disappeared before a saccade (see also Deubel, Bridgeman, & Schneider, 1998; Deubel, Schneider, & Bridgeman, 1996). Demeyer et al (2010) similarly found the most spatiotopic integration between subtly different stimuli when pre- and post-saccadic stimuli were continuously present across a saccade, and this integration disappeared entirely when they were separated by a blank and a mask.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, in our experiment no element was present at the original saccade target position in the search array. A recent study revealed that spatial updating of attention across eye movements depends critically on the continued presence of an object at the attended location both before the saccade and after its landing (Lisi, Cavanagh, & Zorzi, 2015). In our study, without this spatial continuity, attentional benefits might not have been transferred from the saccade target to the subsequent search elements.…”
Section: Landmark Search and Space Constancymentioning
confidence: 50%
“…Yao et al (2016) even find neither remapping nor lingering of attention in a psychophysical study with humans though these results are may be biased by their experimental design where remapped and lingering attention position were not only irrelevant, but importantly these positions were never target locations that tested the amount of attention. Lisi, Cavanagh, and Zorzi (2015) suggest, that spatial updating of attention depends on the setup of the experiment, namely whether visual objects, which can serve as spatial landmarks, are presented or not. In their experiments, they found that the lingering effect vanishes if a placeholder is shown at the attended location for the whole trial.…”
Section: Discussionmentioning
confidence: 99%